Amodiaquine-Artesunate versus Artemether-Lumefantrine against Uncomplicated Malaria in Children Less Than 14 Years in Ngaoundere, North Cameroon: Efficacy, Safety, and Baseline Drug Resistant Mutations in pfcrt, pfmdr1, and pfdhfr Genes. (15th December 2013) - Ali, Innocent M.; Netongo, Palmer M.; Atogho-Tiedeu, Barbara; Ngongang, Eric-Olivier; Ajua, Anthony; Achidi, Eric A.; Mbacham, Wilfred F.
Abstract : Background . In Cameroon, both Artesunate-amodiaquine (AS/AQ) and artemether-lumefantrine (AL) are used as first-line treatment against uncomplicated malaria in line with the WHO recommendations. We compared the efficacy and safety of both therapeutic combinations and determined the prevalence of drug resistance conferring mutations in three parasite genes. Methods . One hundred and fifty acute malaria patients between six months and 14 years of age were randomized to receive standard doses of either AS/AQ (73) or AL (77) and followedup for 28 days. Outcome of treatment was according to the standard WHO classification. DNA samples from pretreatment parasite isolates were used to determine the prevalence of resistant mutations in the pfcrt, pfmdr1, and dhfr genes. Results . Both drug combinations induced rapid clearance of parasites and malaria symptoms. PCR-corrected cure rates were 100% and 96.4% for AL. The combinations were well tolerated. Major haplotypes included CVIET (71%), CVMNT (25%) for the pfcrt ; SND (100%) for the pfmdr1 ; IRN (79, 8%), NCS (8.8%), and mixed haplotype (11, 8%) for the dhfr . Conclusion . Both AS/AQ and AL were highly effective and well tolerated for the treatment of uncomplicated falciparum malaria in Ngaoundere, Cameroon. High prevalence of mutant pfcrt alleles confirms earlier observations. Long-term monitoring of safety and efficacy and molecular markers is highly solicited.